Regulatory T Cells Protect Fine Particulate Matter-Induced Inflammatory Responses in Human Umbilical Vein Endothelial Cells - Wen-cai Zhang; Yan-ge Wang; Zheng-feng Zhu; Fang-qin Wu; Yu-dong Peng; Zhu-yue Chen; Jin-hua Yang; Jing-jing Wu; Yi-tian Lian; Mei-an He; Tang-chun Wu; Long-xian Cheng (Mediators of Inflammation)
Objective. To investigate the role of CD4+CD25+ T cells (Tregs) in protecting fine particulate matter (PM-) induced inflammatory responses, and its potential mechanisms. Methods. Human umbilical vein endothelial cells (HUVECs) were treated with graded concentrations (2, 5, 10, 20, and 40 µg/cm2) of suspension of fine particles for 24h. For coculture experiment, HUVECs were incubated alone, with CD4+CD25− T cells (Teff), or with Tregs in the presence of anti-CD3 monoclonal antibodies for 48 hours, and then were stimulated with or without suspension of fine particles for 24 hours. The expression of adhesion molecules and inflammatory cytokines was examined. Results. Adhesion molecules, including vascular cell adhesion molecule-1 (VCAM-1) and intercellular adhesion molecule-1 (ICAM-1), and inflammatory cytokines, such as interleukin (IL-) 6 and IL-8, were increased in a concentration-dependent manner. Moreover, the adhesion of human acute monocytic leukemia cells (THP-1) to endothelial cells was increased and NF-κB activity was upregulated in HUVECs after treatment with fine particles. However, after Tregs treatment, fine particles-induced inflammatory responses and NF-κB activation were significantly alleviated. Transwell experiments showed that Treg-mediated suppression of HUVECs inflammatory responses impaired by fine particles required cell contact and soluble factors. Conclusions. Tregs could attenuate fine particles-induced inflammatory responses and NF-κB activation in HUVECs.